Effectiveness of Online Based Licensing Services at One Stop Integrated Invesment and Licensing Service of Sumatera Utara Province - Amalia, Gita; Sirojuzilam; Lubis, Irsyad (Journal of Environmental and Development Studies, 2021)
The purpose of this study is to analyze the Community Satisfaction Index (IKM) and the effectiveness on online-based licensing services in the One Stop Integrated Investment and Licensing Service of Sumatera Utara Province. The analytical method used in this study is descriptive quantitative analysis. The results of the study obtained that the Index of Community Satisfaction with online-based licensing services obtained a value of 86.29. Based on KepMenPAN Number: KEP/25/M.PAN/2/2004 on General Guidelines for The Preparation of Community Satisfaction Index of Government Agency Service Units included in the quality of service "A" with the performance of service units "Very Good" because it is at the IKM Conversion Interval Value between 81.26 - 100.00. The effectiveness obtained a value of 86.02% with a very effective category because it is on interpretation of 81-100%.